SUPER (a,d)-EDGE ANTIMAGIC TOTAL LABELING OF CONNECTED TRIBUN GRAPH - Mahmudah, Muhlisatul; Dafik, D; Slamin, S (Department of Mathematics Education , University of Jember, 2015)
Abstract. A G graph of order p and size q is called an (a,d)-edge antimagic total if there exist a bijection f:V(G)∪E(G)⟶1,2,…,p+q such that the edge-weights, w(uv)=f(u)+f(v)+f(uv), uv∈E(G), form an arithmetic sequence with first term a and common difference d. Such a graph G is called super if the smallest possible labels appear on the vertices. In this paper we study super (a, d)-edge-antimagic total properties of connected Tribun graph. The result shows that a connected Tribun graph admit a super(a,d)-edge antimagic total labeling ford=0,1,2 for n≥1. It can be concluded that the result of this research has covered all the feasible n,d. Key Words: (a,d)-edge antimagic vertex labeling, super(a,d)-edge antimagic total labeling, Tribun Graph.